Characterization of the xiamenmycin biosynthesis gene cluster in Streptomyces xiamenensis 318. - Yong Yang (Public Library of Science (PLoS), 2014)
Xiamenmycin (1) is a prenylated benzopyran derivative with anti-fibrotic activity. To investigate the genetic basis of xiamenmycin biosynthesis, we performed genome mining in the xiamenmycin-producing Streptomyces xiamenensis wild-type strain 318 to identify a candidate gene cluster. The complete gene cluster, consisting of five genes, was confirmed by a series of gene inactivations and heterologous expression. Based on bioinformatics analyses of each gene and feeding experiments, we found that the structure of an intermediate xiamenmycin B (3) accumulated in a ximA inactivation mutant, allowing us to propose a biosynthetic pathway. All five of the genes in the pathway were genetically and biochemically characterized. XimA was biochemically characterized as an ATP-dependent amide synthetase, catalyzing an amide bond formation in the presence of ATP as the final step in Xiamenmycin biosynthesis. The Km value of XimA was determined to be 474.38 µM for the substrate xiamenmycin B. These studies provide opportunities to use genetic and chemo-enzymatic methods to create new benzopyran derivatives as potential therapeutic agents.